Pengaruh Pencahayaan Pada Ruang Ganti Terhadap Persepsi Calon Pembeli di Toko Fashion - Chandrahera, Yuma; Suhanjoyo, Shirly Nathania (Program Studi Desain Interior Unikom, 2024)
The process of changing room on fashion products at a retailer that sells products is an important process in determining purchasing decisions. When trying on clothes, potential buyers will make sure whether to buy or not the product they are wearing by considering various factors, and most importantly how the product fits or not. When trying in the dressing room, the interior elements that can affect humans are related to the size of the room, mirrors, interior materials and lighting in the dressing room. Of these several factors, lighting is one of the important factors that can influence perception and can have a certain effect on product appearance. The quality of lighting that needs to be understood is the intensity of the light and the color of the light. In connection with the color temperaturof light that can affect the appearance of the product used and also affect the original color of the product, it is necessary to pay attention to which color temperaturof light is best used in the dressing room of fashion products on the perception of prospective buyers so that they feel appropriate, add to the attractiveness of the product so that strengthen purchase decisions. Keywords: color temperature, lighting design, fashion, product, dressing room